THE MODEL OF HUMAN RESOURCES PERFORMANCE IMPROVEMENT THROUGH EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE BY LEARNING ORIENTATION AS INTERVENING VARIABLE - Nur Laily Monita Arti (UNISSULA, 2018)
The purpose of this research is to analyze and examine between the variables of emotional intelligence, spiritual intelligence and learning orientation to human resources performance in an organization. This research used purposive sampling with 131 people as respondents. Data collection techniques used in this study is questionnaires and interviews. Data analyzed by using SPSS 19 software with regression test to find out the determine of independent variable to dependent variable, independent variable to intervening variable and intervening variable to independent variable. Demonstrate that human resources performance can be improved by increasing the intensity of learning orientation, emotional intelligence, and spiritual intelligence. Learning orientation has a significantly positive influence on human resources performance. While emotional intelligence and spiritual intelligence have a significantly positive influence on human resources performance. So in this research, emotional intelligence, spiritual intelligence and learning orientation have a significantly positive influence on human resources performance.Keywords : emotional intelligence, spiritual intelligence and learning orientation, human resources performance